2002
DOI: 10.1007/s12043-002-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of absorbed pump power on the quality of output beam from monolithic microchip lasers

Abstract: The dependence of the beam propagation factor (M 2 parameter) with the absorbed pump power in the case of monolithic microchip laser under face-cooled configuration is extensively studied. Our investigations show that the M 2 parameter is related to the absorbed pump power through two parameters (α and β ) whose values depend on the laser material properties and laser configuration. We have shown that one parameter arises due to the oscillation of higher order modes in the microchip cavity and the other parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the context of classical laser concepts, an increase in the output power might occur together with a decrease in the beam quality (an increase of M 2 ), and therefore, the brightness does not scale trivially. Typically, it decreases with an increase in the pump as observed for microchip solid-state lasers [4,5] and semiconductor systems [6,7]. This is because it exceeds the generation threshold for higher-transverse modes characterized by higher divergence [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…In the context of classical laser concepts, an increase in the output power might occur together with a decrease in the beam quality (an increase of M 2 ), and therefore, the brightness does not scale trivially. Typically, it decreases with an increase in the pump as observed for microchip solid-state lasers [4,5] and semiconductor systems [6,7]. This is because it exceeds the generation threshold for higher-transverse modes characterized by higher divergence [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…In the context of classical laser concepts, an increase in the output power might occur together with a decrease in the beam quality (an increase of ), and therefore, the brightness does not scale trivially. Typically, it decreases with an increase in the pump as observed for microchip solid-state lasers [ 4 , 5 ] and semiconductor systems [ 6 , 7 ]. This is because it exceeds the generation threshold for higher-transverse modes characterized by higher divergence [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mukhopadhay et al have theoretically investigated the effect of absorbed pump power on the quality of output beam for a facecooled monolithic laser. 35 They have considered the effect of change in mode volume as well as the spherical aberration associated with the thermal lens as a function of the absorbed pump power which causes the degradation of the output beam quality from Nd 3+ doped GdVO 4 monolithic lasers. 35 Sudheer et al have reported characterization of solid-state laser sources for light detection and ranging as well as free space communication applications.…”
Section: Introductionmentioning
confidence: 99%